Beri-beri: the major cause of infant mortality in Karen refugees. - Luxemburger, C; White, N; ter Kuile, F; Singh, H; Allier-Frachon, I; Ohn, M; Chongsuphajaisiddhi, T; Nosten, F (2003)
During a prospective evaluation of malaria prophylaxis in pregnancy in a refugee population on the north-western border of Thailand from 1987 to 1990, an extremely high infant mortality rate (18%) was documented despite good access to health care. Infantile beri-beri was recognized as the main cause of death accounting for 40% of all infant mortality. Thereafter, severe vitamin B1 deficiency in infants was diagnosed and treated promptly. The impact of this was assessed prospectively from 1993 to 1996 in a second cohort study. The case fatality of infantile beri-beri fell from almost 100% to 7%. The overall infant mortality rates declined from 183 to 78 per 1000 live births. Post-neonatal deaths fell by 79% (95% CI 65-87%) while neonatal mortality remained unchanged. Mortality resulting from acute respiratory infections did not change (15 and 11 per 1000, respectively), whereas mortality attributable to beri-beri decreased from 73 to 5 per 1000 (P < 0.0001). Before its recognition approximately 7% of all infants in this population died from infantile beri-beri. This lethal but preventable syndrome may be more common than hitherto recognized, particularly in refugee populations, in this populous region.